2003
DOI: 10.1038/nature01786
|View full text |Cite
|
Sign up to set email alerts
|

P2X4 receptors induced in spinal microglia gate tactile allodynia after nerve injury

Abstract: experiments in Fig. 5, the cultured microglia (see Supplementary Figure) that had been preincubated with or without ATP (50 mM) were injected intrathecally in normal rats (see Supplementary Methods for full details). Immunohistochemistry Transverse L5 spinal cord sections (30 mm) were cut and processed for immunohistochemistry with anti-P2X4R antibody (Alomone). Identification of the type of P2X 4 R-positive cells was performed with the following markers: for microglia, OX42 (Chemicon) and iba1 (a gift from S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
1,372
4
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,401 publications
(1,435 citation statements)
references
References 26 publications
47
1,372
4
12
Order By: Relevance
“…It was shown that PNI‐induced pain hypersensitivity depends on ongoing purinergic signaling through microglial P2X4Rs. A marked reduction in neuropathic pain in both mice knocked down and knocked out of P2X4R further demonstrated the necessity of P2X4Rs51, 52, 53. Intrathecal delivery of P2X4R‐stimulated microglia caused normal rats to produce allodynia, indicating the sufficiency of P2X4R14, 51.…”
Section: Spinal Microglia Are Crucial For Neuropathic Painmentioning
confidence: 87%
“…It was shown that PNI‐induced pain hypersensitivity depends on ongoing purinergic signaling through microglial P2X4Rs. A marked reduction in neuropathic pain in both mice knocked down and knocked out of P2X4R further demonstrated the necessity of P2X4Rs51, 52, 53. Intrathecal delivery of P2X4R‐stimulated microglia caused normal rats to produce allodynia, indicating the sufficiency of P2X4R14, 51.…”
Section: Spinal Microglia Are Crucial For Neuropathic Painmentioning
confidence: 87%
“…Hypoxia induced AMC activation as reflected by increased production of TNF-α and IL-1β was suppressed following the application of PPADS and TNP-ATP, the selective blocker of P2X1-3, 5-7 and P2X1-7 [16], respectively. It is noteworthy that the external morphology of AMC returned to its resting state after treatment with both blockers suggesting that the latter can reduce activation of microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the upregulation of P2X4 in microglia appears to play a crucial role in contributing to neuropathic pain which has a close relationship with the inflammation [15]. Suppression of P2X4 expression by 2', 3'-0-(2, 4, 6-Trinitrophenyl) adenosine 5'-triphosphate) (TNP-ATP) and pyridoxal phosphate-6-azo (benzene-2, 4-disulfonic acid) (PPADS) prevents tactile allodynia [16]. Guo [17] had reported that P2X4 expression in experimental autoimmune encephalomyelitis (EAE) was confined to the macrophage cells that infiltrated from the blood, furthermore, P2X4 expression reflects the inflammation response during EAE.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, in last several years, we have seen several potential markers, such as the ATP receptor P2X4 (Tsuda et al, 2003), the chemokine receptors CCR2 (Abbadie et al, 2003) and CX3CR1 Zhuang et al, 2007), as well as Toll-like recepotor-4 (TLR4) (Tanga et al, 2005).…”
Section: Microglia Activation and Proliferation In The Spinal Cord Inmentioning
confidence: 99%
“…Later, it was found that spinal injection of an glial inhibitor fluorocitrate can reduce hyperalgesia (Meller et al, 1994). However, the specific role of microglia in nerve injury-induced neuropathic pain was demonstrated a decade later (Tsuda et al, 2003). Glial activation has been studied in different animal models such as neuropathic pain after injuries to peripheral nerves (Colburn et al, 1997) or the spinal cord (Hains & Waxman, 2006), inflammatory pain after injection of inflammatory substances (e.g.…”
Section: Introductionmentioning
confidence: 99%